Changes in tissue oxygen saturation with calf compression sleeve: before, during and after a cycling exercise - Boucourt, B.; Bouhaddi, M.; Mourot, L.; Tordi, N.; Menetrier, A. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The purpose of this study was to examine the changes in tissue oxygen saturation (StO2) with calf compression sleeves, before, during and after a cycling exercise.